Co-designing a mobile application to reduce self-stigma for people with opioid use disorder during pregnancy and the postpartum period - Osweiler, Bailey W.; Rammaha, Thue; Szlyk, Hannah S.; Dell, Nathaniel A.; Macon, Jushawn; Jacobson, Nicholas C.; Burley, Casey; Goodman, Micah; Cavazos-Rehg, Patricia A.; Ramsey, Alex T. (Frontiers in Psychiatry, 2025)
AimsPregnant and postpartum individuals (PPI) face unique challenges to recovery from opioid use disorder (OUD), including stigma from self and others. Enhearten is a mobile application featuring an ecological momentary intervention to reduce self-stigma and provide support for perinatal individuals with OUD. This study aimed to refine and test Enhearten using the Discover, Design/Build, and Test (DDBT) framework. We hypothesized that DDBT would be associated with increased intervention acceptability, and Enhearten would be associated with decreased self-stigma among PPI with OUD.MethodsIn this fully-remote study, participants provided human-centered design feedback in semi-structured interviews at 1-month to guide adaptations. Participants also completed structured questionnaires including validated measures of self-stigma at baseline, 1-month, and 2-month follow-ups and technology acceptance at 1-month and 2-month follow-ups. Paired samples t-tests determined whether differences existed between baseline and 2-month self-stigma and between 1-month and 2-month technology acceptance.ResultsTwenty PPI (40% pregnant, 60% postpartum) representing diverse geographic U.S. regions used Enhearten. Qualitative findings highlighted the value of peer support and positive framing but revealed modifiable barriers and a desire for additional features. Human-centered design feedback guided adaptations, including added discussion group features and enhanced relevance of messages. Quantitatively, self-stigma decreased from baseline (M=2.70, SD=0.47) to 2-month (M=2.27, SD=0.61), t(19)=-2.902, p=0.009 (Cohen’s d=0.742). Technology acceptance was high at 1-month and increased by 2-month, t(15)=3.211, p=0.006.ConclusionsThese results support the potential of digital interventions to reduce self-stigma and improve perinatal OUD recovery outcomes. The DDBT framework provides structure to understand lived experiences, adapt rapidly, and evaluate digital intervention efficacy.